Comunicación, clima y cultura organizacional para la gestión del conocimiento. Pymes metalmecánicas de Cali. - Dario Quiroga Parra (Universidad y Empresa, 2007)
The climate, culture, and organizational communication are directorship variables which facilitate enterprise results to accomplish its goals, producing distinctive competences and competitive advantages through the knowledge management for innovations; with the appropriate use of information provided by the ICT. The results have come out from two researches on the metal mechanical industrial sector allow the reader to know how the Pymes use these variables on their development management. The document concludes that there are many cognitive, managerial, economic and technological limitations to improve the productivity and competitiveness processes, due to the lack of experience on these topics and of the managerial models used.